Evolving Trends in Communication Technology for Persons with Disabilities - Restianty, Ajani; Sumartias, Suwandi; Hadisiwi, Purwanti; Hafiar, Hanny (Jurnal Pustaka Komunikasi, 2024)
The goal has been to conduct a global analysis of communication technology for people with disabilities. As a result, the purpose of this research is to categorize issues and concepts connected to the study of technological innovation. 6204 indexed papers from Scopus, issued by major publishers such as Springer, Emerald, Sage, MDPI, Taylor Francis, and ScienceDirect, were collected through descriptive analysis. The findings classified topics in the research of communication technology for people with disabilities into five categories: disability, disabled person, communication, adolescent, and education. Furthermore, it is linked to crucial concerns such as accessibility, quality of life, interpersonal communication, hearing impairment, and learning. This study implies how the conceptual findings of a study on communication technology for people with disabilities may assist in the development of a conceptual framework for future research. The study's limitation is that peer-reviewed publications were only acquired from the Scopus database. As a result, recommendations for future research necessitate the use of a comparative analytic approach, such as Scopus Databases and Web of Science (WoS).